2013
DOI: 10.1016/j.jvs.2013.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hospital volume and type on outcomes of open and endovascular repair of descending thoracic aneurysms in the United States Medicare population

Abstract: The total number of DTA repairs has significantly increased. Operative mortality for TEVAR is independent of hospital volume and type, whereas mortality after open surgery is lower at HV hospitals, suggesting that TEVAR can be safely performed across a spectrum of hospitals, whereas open surgery should be performed only at HV hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 24 publications
0
23
1
1
Order By: Relevance
“…Although to our knowledge the association between hospital volume and patient outcomes has begun to be examined only recently for patients with sarcomas, it has been extensively examined across other patient populations. [6][7][8]11,20,26 Compared with treatment at LVHs, treatment at HVHs has been associated with improved patient outcomes after various complex oncologic resections, including head and neck surgery, 12 esophagectomy, 9,15,16 colorectal surgery, 9,17,27 HPB,9,19,20,28 cystectomy, 13 nephrectomy, 10 and major lung resection. 14 The relationship between hospital volume and patient outcomes may reflect differences in multiple aspects of the multidisciplinary care of the oncology patient undergoing complex surgical resection, such as the patient with primary resectable RPS.…”
Section: Discussionmentioning
confidence: 99%
“…Although to our knowledge the association between hospital volume and patient outcomes has begun to be examined only recently for patients with sarcomas, it has been extensively examined across other patient populations. [6][7][8]11,20,26 Compared with treatment at LVHs, treatment at HVHs has been associated with improved patient outcomes after various complex oncologic resections, including head and neck surgery, 12 esophagectomy, 9,15,16 colorectal surgery, 9,17,27 HPB,9,19,20,28 cystectomy, 13 nephrectomy, 10 and major lung resection. 14 The relationship between hospital volume and patient outcomes may reflect differences in multiple aspects of the multidisciplinary care of the oncology patient undergoing complex surgical resection, such as the patient with primary resectable RPS.…”
Section: Discussionmentioning
confidence: 99%
“…This has been consistent with recent reports on the population studies. [12][13][14] Of considerable interest was the effect of endovascular option on the risk profile of aneurysms that continued to be treated with open repair. Although this effect was difficult to measure directly, to assess the potential effect of case complexity, we divided our surgical cohort …”
Section: Discussionmentioning
confidence: 99%
“…2 Since that report, we observed that the presenting disposition of our patients has changed, which may have been the result of the shift from open to endovascular treatments of the thoracic aorta. [12][13][14] In addition, our technique has evolved, incorporating changes in monitoring and organ protection. [15][16][17] Thus, the purpose of this report was to reexamine our experience with open thoracic and TAAA repair to determine the potential impact of the changes on mortality and morbidity.…”
mentioning
confidence: 99%
“…Settepani et al 1showed a 5% mortality rate in a systematic literature review covering the last ten years. Nevertheless, data from the National Impatient Sample (9,10) and the Medicare Provider Analysis and Review (11,12) reflect very different results, with worldwide mortality rates ranging from 15% to 20%.…”
Section: Current Resultsmentioning
confidence: 99%